2018
DOI: 10.1002/bmc.4378
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals, fungicide quintozene and its hazardous impurity residues in medical Panax notoginseng (Burk) F.H.Chen root

Abstract: A quick, easy, cheap, effective, rugged, and safe extraction approach and gas chromatography/tandem mass spectrometry with programmed temperature vaporization sampling technology were used to determine fungicide quintozene and its hazardous impurity hexachlorobenzene (HCB) in Panax notoginseng root, which is commonly used as a rare traditional Chinese medicine worldwide. The mean recoveries were in the ranges of 94-125 and 84-119% for quintozene and HCB with relative standard deviations of 6.2-16.1% at three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Then, 5 mL of filter solution was used for the determination of the Cd concentration. Similar steps were described by Geng et al [44]. The Cd reference value is shown in Table 2.…”
Section: The Determination Of CD Reference Valuementioning
confidence: 87%
“…Then, 5 mL of filter solution was used for the determination of the Cd concentration. Similar steps were described by Geng et al [44]. The Cd reference value is shown in Table 2.…”
Section: The Determination Of CD Reference Valuementioning
confidence: 87%
“…The highest content was dimethomorph detected in Dendrobium o cinale Kimura et Migo, that was 6.11 mg/kg (Xu et al 2021). The lowest was HCB in Panax notoginseng (Burk) F.H.Chen root, and the content was 0.006 mg/kg (Geng et al 2019). Quintozene in Panax notoginseng was the fungicide with the highest exceeding rate up to 40% (Fu et al 2020).…”
Section: Pesticides In Tcmmentioning
confidence: 99%
“…[118] they suggested that, the use of microbial resources as a promising alternative to traditional fertilizers and pesticides due to their economic efficiency, environmental safety, and non-toxic nature. The deterioration of soil quality is accelerated by emissions from industrial waste, widespread fertilizer and pesticide use, and sewage irrigation, leading to issues like soil hardening, salinization, and accumulation of heavy metals and organic contaminants [119,120]. A national survey in China revealed that 16.1% of soil sites investigated had excessive levels of pollutants, including both inorganic and organic contaminants [121].…”
Section: Soil Remediation With Phytobeneficial Bacteriamentioning
confidence: 99%